PERBEDAAN NYERI POST OPERASI SECTIO CAESAREA DENGAN TRANVERSUS ABDOMINIS PLANE (TAP) BLOCK DAN INVILTRASI LIDOCAINE - Nailul Istiqomah; Tophan Heri Wibowo; Madyo Maryoto (Jurnal Cakrawala Ilmiah, 2023)
: The incidence of sectio caesarea in Indonesia is 17.6%. After sectio caesarea, in addition to pain from abdominal incisions and side effects of anesthesia, it causes moderate to severe postoperative pain as a result of uterine and somatic pain in the abdominal wall. Currently there are many of the safest and most effective ways of intervention for post-cesarean pain management such as transversus abdominis plane block (TAP) anesthesia and lidocaine infiltration. This study aims to determine the differences in Postoperative Sectio caesarea Pain with TAP Block and Lidocaine Infiltration.The type of research in this study was quantitative with the research design using a clinical trial with a nonequivalent group posttest only design. This research was conducted at Bumi Waras Hospital in Bandar Lampung in June 2022. The number of samples in each group was 20 samples, namely 10 samples for the group that received the Transversus Abdominis Plane (TAP) Block and 10 samples for the group that received lidocaine infiltration using the sampling technique. was total sampling. The research instrument used in this study was in addition to the observation sheet on the use of anesthesia in cesarean section patients, the researcher also used a nyer observation sheet using the Numeric Rating Scale (NRS) and data analysis was carried out using the SPSS version 23 with the Mann Whitney test. The results of the study showed that there were differences in Postoperative Sectio caesarea Pain with TAP Block and Lidocaine Infiltration at Bumi Waras Hospital Bandar Lampung with a p-Value <α (0.003 <0.05). The results of this study are expected to be input for hospitals to improve services for patients experiencing postoperative pain